2014
DOI: 10.1084/jem.20131289
|View full text |Cite
|
Sign up to set email alerts
|

Sex steroid blockade enhances thymopoiesis by modulating Notch signaling

Abstract: Velardi et al. show that sex steroids regulate thymopoiesis by directly modulating Notch signaling, and provide a novel clinical strategy to boost immune regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
91
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(99 citation statements)
references
References 40 publications
3
91
1
Order By: Relevance
“…Sex steroids influence thymopoiesis through direct inhibition of Notch ligand in cortical thymic epithelial cells. In accordance with previous findings that Notch ligand is critical for commitment and differentiation of T-cell progenitors, sex steroid ablation by LHRH receptor antagonism enhanced expression of Notch ligand, resulting in rapid promotion of thymopoiesis [7]. Therefore, these strategies could not only improve thymic regeneration after allo-HSCT but also boost immune function.…”
Section: Novel Strategies For Allo-hsctsupporting
confidence: 88%
“…Sex steroids influence thymopoiesis through direct inhibition of Notch ligand in cortical thymic epithelial cells. In accordance with previous findings that Notch ligand is critical for commitment and differentiation of T-cell progenitors, sex steroid ablation by LHRH receptor antagonism enhanced expression of Notch ligand, resulting in rapid promotion of thymopoiesis [7]. Therefore, these strategies could not only improve thymic regeneration after allo-HSCT but also boost immune function.…”
Section: Novel Strategies For Allo-hsctsupporting
confidence: 88%
“…As a consequence, efforts to improve thymic reconstitution using cytokines [IL7 (25), SCF, KFG (26,27), FLT3L (28)] or hormones [growth hormone (29), thyroid-stimulating hormone (30), and ablation of sex hormones (31)] are only likely to be effective if they selectively act on the thymic microenvironment or mimic signals given by the thymic epithelial cells to developing thymocytes. Transplantation of committed T-cell progenitors together with HSCT, as shown before with mouse hematopoietic cells cultured ex vivo on OP9-DL1 expressing stromal supportwhich provide the cells with the Notch signals required to direct T-cell development (32)-as well as diminishing the influence of male sex hormones known to deregulate intrathymic Notch ligand DLL4 (31) may work well to improve thymic function and support diverse TCR repertoire formation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, sex steroids in the thymus seem to decrease the expression of Notch ligand, which is an important driver of T-cell development. 59 Studies both in man and mouse demonstrated that SSA using castration (in mice) or the luteinizing hormone releasing hormone (LHRH) agonist Leuprolide after auto-and allo-HSCT or cytoablative therapy per se results in: (1) increased numbers of lymphoid precursors and import of thymic precursors into the thymus, (2) improved thymopoiesis, (3) enhanced B lymphopoiesis, and (4) improved recovery of functional immunity. 51 As mentioned above, a clinical trial combining SSA with leuprolide and KGF in HSCT recipients is underway.…”
Section: Sex Steroid Ablation (Ssa)mentioning
confidence: 99%